Differential patterns of connectivity in Western Pacific hydrothermal vent metapopulations: A comparison of biophysical and genetic models. (9th December 2021) - Breusing, Corinna; Johnson, Shannon B.; Mitarai, Satoshi; Beinart, Roxanne A.; Tunnicliffe, Verena
Abstract: Hydrothermal ecosystems face threats from planned deep‐seabed mining activities, despite the fact that patterns of realized connectivity among vent‐associated populations and communities are still poorly understood. Since populations of vent endemic species depend on larval dispersal to maintain connectivity and resilience to habitat changes, effective conservation strategies for hydrothermal ecosystems should include assessments of metapopulation dynamics. In this study, we combined population genetic methods with biophysical models to assess strength and direction of gene flow within four species of the genus Alviniconcha ( A .  boucheti, A .  kojimai, A .  strummeri and A .  hessleri ) that are ecologically dominant taxa at Western Pacific hydrothermal vents. In contrast to predictions from dispersal models, among‐basin migration in A .  boucheti occurred predominantly in an eastward direction, while populations within the North Fiji Basin were clearly structured despite the absence of oceanographic barriers. Dispersal models and genetic data were largely in agreement for the other Alviniconcha species, suggesting limited between‐basin migration for A .  kojimai, lack of genetic structure in A .  strummeri within the Lau Basin and restricted gene flow between northern and southern A .  hessleri populations in the Mariana back‐arc as a result of oceanic current conditions. Our findings show that gene flow patterns in ecologically similar congeneric species can be remarkably different and surprisingly limited depending on environmental and evolutionary contexts. These results are relevant to regional conservation planning and to considerations of similar integrated analyses for any vent metapopulations under threat from seabed mining.